Gambaran Social Comparison Pengguna Fitur Instastory pada Aplikasi Instagram di Kalangan Mahasiswa - Sudjarwo, andika Bramastha; Handayani, Panca Kursistin; Linsiya, Ria Wiyatfi (Indonesian Journal Publisher, 2024)
Instastory is a feature in the Instagram application which is widely used by users of the application, one of which is students. Generally, students fall into the category of early adulthood where individual self-development is at its peak and they have a high sense of competition. Sometimes through Instagram stories students use other people to gain an understanding of themselves. Social Comparison is a process of self-comparison carried out by individuals with other individuals. Individuals compare themselves because these individuals need external standards obtained from other people so that it will produce an assessment within the individual. This research aims to find out about the social comparison behavior of students who use the Instagram story feature on the Instagram application. This type of research is quantitative with descriptive analysis. The population in this research is students who use the Instagram story feature in Jember Regency with a total sample of 349 students. The scale used is INCOM (Iowa Netherlands Comparison Orientation Scale) which has been translated into Indonesian by Amelia (2019) (11 items; α= 0.793). The research results show that students tend to carry out social comparisons. If we look at both ability and opinion, both show a high category level. Through Instagram stories, students tend to make social comparisons with their peers in terms of lifestyle, wealth, personal achievements and outfits.